Current status and potential of morphometric sperm analysis - Maroto-Morales, Alejandro; García-Álvarez, Olga; Ramón, Manuel; Martínez-Pastor, Felipe; Fernández-Santos, M Rocío; Soler, A Josefa; Garde, José Julián (Asian journal of andrology, 2016)
The spermatozoon is the most diverse cell type known and this diversity is considered to reflect differences in sperm function. How the diversity in sperm morphology arose during speciation and what role the different specializations play in sperm function, however, remain incompletely characterized. This work reviews the hypotheses proposed to explain sperm morphological evolution, with a focus on some aspects of sperm morphometric evaluation; the ability of morphometrics to predict sperm cryoresistance and male fertility is also discussed. For this, the evaluation of patterns of change of sperm head morphometry throughout a process, instead of the study of the morphometric characteristics of the sperm head at different stages, allows a better identification of the males with different sperm cryoconservation ability. These new approaches, together with more studies employing a greater number of individuals, are needed to obtain novel results concerning the role of sperm morphometry on sperm function. Future studies should aim at understanding the causes of sperm design diversity and the mechanisms that generate them, giving increased attention to other sperm structures besides the sperm head. The implementation of scientific and technological advances could benefit the simultaneous examination of sperm phenotype and sperm function, demonstrating that sperm morphometry could be a useful tool for sperm assessment.
Keywords: Sperm Motility; spermie; tvar buňky; Image Processing, Computer-Assisted; Cell Shape; mužské pohlaví; analýza spermatu; motilita spermií; Semen Analysis; Humans; Spermatozoa; hlavička spermie; Male; Sperm Head; lidé; počítačové zpracování obrazu